Condom use in prevention of Human Papillomavirus infections and cervical neoplasia: systematic review of longitudinal studies. (March 2014) - Lam, Janni Uyen Hoa; Rebolj, Matejka; Dugué, Pierre-Antoine; Bonde, Jesper; von Euler-Chelpin, My; Lynge, Elsebeth
Objectives: Based on cross-sectional studies, the data on protection from Human Papillomavirus (HPV) infections related to using male condoms appear inconsistent. Longitudinal studies are more informative for this purpose. We undertook a systematic review of longitudinal studies on the effectiveness of male condoms in preventing HPV infection and cervical neoplasia. Methods: We searched PubMed using MeSH terms for articles published until May 2013. Articles were included if they studied a change in non-immunocompromized women's cervical HPV infection or cervical lesion status along with the frequency of condom use. Results: In total, 384 abstracts were retrieved. Eight studies reported in 10 articles met the inclusion criteria for the final review. Four studies showed a statistically significantly protective effect of consistent condom use on HPV infection and on regression of cervical neoplasia. In the remaining four studies, a protective effect was also observed for these outcomes, although it was not statistically significant. Conclusions: Consistent condom use appears to offer a relatively good protection from HPV infections and associated cervical neoplasia. Advice to use condoms might be used as an additional instrument to prevent unnecessary colposcopies and neoplasia treatments in cervical screening, and to reduce the risk of cervical cancer.